Biosensors based on DNA logic gates. Issue 2 (28th November 2020) - Yin, Fangfei; Wang, Fei; Fan, Chunhai; Zuo, Xiaolei; Li, Qian
Abstract: Abstract Biosensor is a device that responds to a particular target in a selective way by incorporation of biological recognition as sensing unit. For practical biomedical applications, a digital output (a qualitative YES/NO answer) is highly demanded for certain end‐user or point‐of‐care applications. Boolean logic, which can be applied to any type of information expressed as 0 (NO) and 1 (YES), is widely employed to achieve such qualitative analysis. Over the past decade, owing to DNA's advantages of stability, accessibility, and manipulability, significant research efforts have been focused on the design and application of DNA logic gates (DLG)‐based biosensors capable of implementing logic‐gated biomedical functions. This review summarizes the existed representative examples and the advanced developments of DLG biosensors, and discusses the limitations and the future directions on the development of novel nanosensors based on DNA logic operations for realizing highly efficient diagnosis. Abstract : This review gives a brief overview of biosensors based on DNA logic gates, focusing on parameters such as the rational design, inputs and outputs, logic gating operation, outputs readout and instrumentation. Current challenges and future potential for DNA logic gates biosensors are also discussed.